Answer

Verified

374.1k+ views

**Hint:**We have been given to find the horizontal intercept. Horizontal intercept is the $x - axis$. Put the value of $y = 0$ in the given equation. Then, we will get the equation in the terms of $x$ - intercept and solve it by splitting the middle term.

**Complete step by step solution:**

From the question, we know that we have to find the horizontal intercept of the equation $y = - 4{x^2} - 8x + 12$ by the method of algebra. We know that the horizontal intercept is the intercept of the $x - axis$ whereas the vertical intercept is the $y - axis$. So, we have to find the equation which gives us the value of $x$.

Every point on the $x - axis$ has the form of $\left( {x,0} \right)$ , while every point on the graph has the form $\left( {x,f\left( x \right)} \right)$, as $f\left( x \right) = y$, so, to find the $x$ intercept we have to put the value of $y = 0$.

Therefore, putting $y = 0$ in the above equation, we get –

$

\Rightarrow 0 = - 4{x^2} - 8x + 12 \\

\Rightarrow 4{x^2} + 8x - 12 = 0 \\

$

Now, taking 4 as common from the above equation to make the equation more simplified –

$ \Rightarrow {x^2} + 2x - 3 = 0 \cdots \left( 1 \right)$

Now, we have three parts –

The first term, ${x^2}$, has the coefficient as 1.

The middle term, $2x$, has the coefficient as 2.

The last term, $ - 3$, has the coefficient as -3.

Multiply the coefficient of the first term which is 1 with the last term or constant which is -3 –

$ \Rightarrow 1 \times \left( { - 3} \right) = - 3$

Now, the factors of -3 are -1 and 3 which when multiplied gives the result as -3 and sum as 2 –

$ \Rightarrow - 1 + 3 = 2$

Putting these values in the equation (1), we get –

$ \Rightarrow {x^2} + 3x - x - 3 = 0$

Taking like terms from the first two-term and taking common factor from the last two terms –

$ \Rightarrow x\left( {x + 3} \right) - 1\left( {x + 3} \right) = 0$

Now, $\left( {x + 3} \right)$ is common in the above equation –

$ \Rightarrow \left( {x + 3} \right)\left( {x - 1} \right) = 0$

When $\left( {x + 3} \right) = 0$ then, $x = - 3$

When $\left( {x - 1} \right) = 0$ then, $x = 1$

**Hence, the horizontal intercepts of the equation are $\left( { - 3,0} \right)$ and $\left( {1,0} \right)$.**

**Note:**

We can also find the horizontal intercepts by finding the discriminant and then nature of roots. Then, use the quadratic formula for the equation ${x^2} + 2x - 3 = 0$ and find the values of $x$ by using the formula –

$x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$

where, $a$ is the coefficient of the first term, $b$ is the coefficient of the middle term and $c$ is the constant term.

Recently Updated Pages

In the equation x2+y2+2gx+2fy+c0 represents a circle class 10 maths CBSE

How do you Factor completely 2x3 + 5x2 37x 60 class 10 maths CBSE

How do you prove the identity dfrac11 cos x + dfrac11 class 10 maths CBSE

How do you solve 2x2 5x 12 0 by completing the squ class 10 maths CBSE

How do you solve 2x+46 class 10 maths CBSE

How do you simplify dfracm42m4 and write it using only class 10 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write the 6 fundamental rights of India and explain in detail

Name 10 Living and Non living things class 9 biology CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths